Endocrine Disruptors (IntechOpen, 2023)
The World Health Organization estimated that each year there are more than 13 million deaths caused by environmental causes. Exposure to endocrine disrupting chemicals (EDCs) during development may cause long-term health outcomes. This book, Endocrine Disruptors, includes eight chapters that illustrate potential endocrine-disrupting activities in water, sediments, crops, animals, and humans. This book assesses the relationship between the EDCs and development, reproduction, or obesity. Finally, detection of the levels of EDCs by autobioluminescent cellular bioreporters is discussed. Scientists, physicians, neuroendocrinologists, neurotoxicologists, and lay readers who have engaged in EDC studies or practice will discover that this book offers insight into all areas of EDC research.